The Fundamental Contradiction of An Emerging System of Corporate Governance in Ukraine - Vladimir Kublikov (CES Working Papers, 2013)
In the article, the key features of development of national corporate case frame in Ukraine are considered. It is retained that the legislation of Ukraine from point of presence of the formal generally accepted measures on defiance of rights for a shareholder can be appraised as highly developed enough. Thus, the personal touch of redistribution of equity in the Ukrainian corporate sector is prevailing of property of insiders. The folded situation allows talking about steady and fundamental contradiction of the formed national system of corporate management.
Keywords: G34; G28; 330; corporate government legislation; financial system of Ukraine; insider's ownership; ownership's structure; shareholders' rights Romania